The Application of Combined Visible and Ultraviolet Irradiation to Improve the Functional Characteristics of Gas Sensors Based on ZnO/SnO2 and ZnO/Au Nanorods - Alexandra P. Ivanishcheva; Victor V. Sysoev; Khabibulla A. Abdullin; Andrey V. Nesterenko; Soslan A. Khubezhov; Victor V. Petrov (Chemosensors, 2023)
Arrays of zinc oxide (ZnO) nanorods were synthesized over quartz substrates by the hydrothermal method. These nanorods were grown in a predominantly vertical orientation with lengths of 500–800 nm and an average cross-sectional size of 40–80 nm. Gold, with average sizes of 9 ± 1 nm and 4 ± 0.5 nm, and tin nanoclusters, with average sizes of 30 ± 5 nm and 15 ± 3 nm, were formed on top of the ZnO nanorods. Annealing was carried out at 300 °C for 2 h to form ZnO/SnO2 and ZnO/Au nanorods. The resulting nanorod-arrayed films were comprehensively studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectrometry (EDS) and X-ray photoelectron spectroscopy (XPS). To fabricate resistive sensor elements, the films were supplied with V/Ni contact metallization on top of the nanorods. The gas sensor performance of the prepared films was evaluated at various temperatures in order to select 200 °C as the optimum one which enabled a selective detection of NO2. Adding UV-viz irradiation via a light-emitting diode, λ = 400 nm, allowed us to reduce the working temperature to 50 °C and to advance the detection limit of NO2 to 0.5 ppm. The minimum response time of the samples was 92 s, which is 9 times faster than in studies without exposure to UV-viz radiation.